Islamic index, independent commissioner and firm performance - Vidia Gati; Mohammad Nasih; Dian Agustia; Iman Harymawan (Cogent Business & Management, 2020)
The prime objective of this study is to examine the effect of Sharia firms and their performance in Indonesia. Sharia is the set of personal and societal behaviour derived from Islam. A firm is included in a sharia firm if it complies with Islamic values. The sample used in this study are firms that are consistently listed on the Sharia-compliant Stock Index (ISSI) in the 2012-2018 period. The result shows that Sharia firms have better performance compared to non-Sharia firms. Additionally, Sharia firms with a smaller size of independent commissioners are associated with higher performance. These positive results indicate that Sharia positioning can improve performance and this is empirical evidence that the ethical firm has a significant influence on the performance.
Keywords: 650; independent commissioner; performance; sharia firm